Tingkat Kecukupan Modal, Pertumbuhan Kredit, dan Risiko Operasional Pada Profitabilitas Lembaga Perkreditan Desa - Darmawan, Kadek; Suartana, I Wayan (E-Jurnal Akuntansi, 2018)
National development focuses on rural communities who play an important role in economic activities in rural areas where financing and credit activities are carried out to support development. One of the efforts of the Provincial Government of Bali to support the economic development of rural communities is by developing financial institutions for rural communities known as the Lembga Perkreditan Desa. This study is intended to find out whether capital adequacy, credit growth, and operational risk affect the ability of LPDs in Gianyar Regency to earn profits in 2015-2017. To answer these problems this study uses 213 data samples and data analysis techniques, namely multiple linear regression. Based on the results of multiple regression analysis, it is known that the F test results and t test results show that capital adequacy, and credit growth have a positive effect and operational risk has a negative effect on the profitability of the Village Credit Institution (LPD) in Gianyar Regency for the 2015-2017 period. Keywords : CAR, BOPO, ROA, profitability